Historicizing IQ Testing : Intelligence Assessments and Their Role in Norwegian Society From the 1900s to the Present - Håkon Aamot Caspersen; Jon Røyne Kyllingstad (Open Book Publishers, 2026)
Intelligence testing has shaped modern society in profound ways, influencing education, psychology, law, and governance. This volume offers the first comprehensive study of the history of IQ testing in a Nordic country, shedding new light on its development, adaptation, and societal impact in Norway. By tracing the evolution of intelligence tests—from their role in schools and special education to forensic psychiatry and criminal law—the book uncovers the tensions surrounding their use. Are these tests instruments of empowerment or tools of control? How have they shaped access to education, healthcare, and legal rights? A key focus of this study is the transnational movement of intelligence tests, particularly between Norway, the USA, and other Nordic nations. It explores how tests have been translated, adapted, standardized, and used, raising questions about their claims to measure universal intelligence. This volume challenges assumptions about IQ testing, placing practices of testing and the tests themselves at the center of historical analysis. By examining the Norwegian case, it contributes fresh insights to international scholarship, offering a vital perspective on the global history of intelligence measurement. Essential reading for historians, psychologists, and educators, this book redefines our understanding of intelligence testing in a changing world.